EFFECT OF VERTICALLY HETEROGENEOUS SOIL SALINITY ON MORPHOLOGICAL CHARACTERISTICS, BIOMASS ACCUMULATION, ROOT DISTRIBUTION, AND TRANSPIRATION OF SUNFLOWER (HELIANTHUS ANNUUS L.) - G. Lei; Q. Zhao; W. Zeng; J. Wu; A. K. Srivastava; C. Ao; C. Song; Y. Wang; J. Huang (Journal of Animal and Plant Sciences, 2020)
Finding out the regulations of crops Morpho-Physiological Characteristics (MPC) to vertical heterogeneous salinity is significant to understand the crop salt tolerance mechanism. An outdoor pot experiment cultivated with sunflower (Helianthus annuus L.; cultivar: LD5009) was conducted at four initial salinity levels (S1: 4.08-9.79, S2: 6.72-11.58, S3: 8.01-13.62, and S4: 10.60-14.31 dS∙m-1), three types of soil salinity distributions (A-type, greater salinity in lower soil; H-type, homogenous salinity; V-type, greater salinity in upper soil) were manually created and maintained by stratified irrigation in each salinity level. Results show the inconsistent inhibitions of salinity levels and distributions on the sunflower MPC, for S2 compared to S1, the MPC reductions were insignificant in V-type, while the maximum leaf area and flower disc diameter, shoot biomass, and transpiration were significantly decreased in A- and H-types (P ≤ 0.05), while the MPC in V-type decreased over than in A-type and resembled with those in H-type for S3 and S4. Consistent with the phenomena of more root biomass distributed in lower salinity soil in salinity heterogeneous treatments, the MPC closely correlated with the minimum salinity (SMin) in potting soil (R2=0.72-0.85), SMin in the lower soil improved sunflower growth more than it in the upper soil when SMin < 9 dS∙m-1 (S2), while the opposite effects were presented if SMin > 9 dS∙m-1 (S3, S4). Therefore, the status of SMin and its vertical position might be important factors for crop salt tolerance determination.
Keywords: Vertical salinity heterogeneity; Sunflower; Morphology; Biomass; Root distribution; Transpiration